Characterization of test positivity among patients with coronavirus disease 2019 (COVID-19) in three electronic health records databases, February-November 2020 - Patrick Saunders-Hastings; Cindy Ke Zhou; Shayan Hobbi; Hui-Lee Wong; Patricia Lloyd; Eva Boyd; Nader Alawar; Tainya C. Clarke; Jeff Beers; Timothy Burrell; Azadeh Shoaibi (BMC, 2022)
Abstract Background Monitoring COVID-19 testing volumes and test positivity is an integral part of the response to the pandemic. We described the characteristics of individuals who were tested and tested positive for SARS-CoV-2 during the pre-vaccine phase of the pandemic in the United States (U.S.). Methods This descriptive study analyzed three U.S. electronic health record (EHR) databases (Explorys, Academic Health System, and OneFlorida) between February and November 2020, identifying patients who received an interpretable nucleic acid amplification test (NAAT) result. Test-level data were used to characterize the settings in which tests were administered. Patient-level data were used to calculate test positivity rates and characterize the demographics, comorbidities, and hospitalization rates of COVID-19-positive patients. Results Over 40% of tests were conducted in outpatient care settings, with a median time between test order and result of 0-1 day for most settings. Patients tested were mostly female (55.6-57.7%), 18-44 years of age (33.9-41.2%), and Caucasian (44.0-66.7%). The overall test positivity rate was 13.0% in Explorys, 8.0% in Academic Health System, and 8.9% in OneFlorida. The proportion of patients hospitalized within 14 days of a positive COVID-19 NAAT result was 24.2-33.1% across databases, with patients over 75 years demonstrating the highest hospitalization rates (46.7-69.7% of positive tests). Conclusions This analysis of COVID-19 testing volume and positivity patterns across three large EHR databases provides insight into the characteristics of COVID-19-tested, COVID-19-test-positive, and hospitalized COVID-19-test-positive patients during the early phase of the pandemic in the U.S.